Psychometric properties of the Spanish version of the hospital anxiety and depression scale in cancer patients - Vilela-Estrada, A.L. (2024)
Background: Although the Hospital Anxiety and Depression Scale (HADS) has been widely studied across various populations, there is still no consensus on its factor structure. This study aims to evaluate the psychometric properties of the HADS in cancer patients.